2008
DOI: 10.1074/jbc.m708638200
|View full text |Cite
|
Sign up to set email alerts
|

γ-Aminobutyric Acid (GABA) and Pentobarbital Induce Different Conformational Rearrangements in the GABAA Receptor α1 and β2 Pre-M1 Regions

Abstract: ␥-Aminobutyric acid (GABA) binding to GABA A receptors (GABA A Rs) triggers conformational movements in the ␣ 1 and ␤ 2 pre-M1 regions that are associated with channel gating. At high concentrations, the barbiturate pentobarbital opens GABA A R channels with similar conductances as GABA, suggesting that their open state structures are alike. Little, however, is known about the structural rearrangements induced by barbiturates. Here, we examined whether pentobarbital activation triggers movements in the GABA A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…Direct activation of the N265C mutant by pentobarbital did not differ from the wild type and was not altered after OMTS was applied. These findings are supported by previous work proposing that the pre-TM1 region of the ␤ 2 subunit contributes to a pentobarbital-mediated activation pathway (Mercado and Czajkowski, 2008).…”
Section: Discussionsupporting
confidence: 81%
“…Direct activation of the N265C mutant by pentobarbital did not differ from the wild type and was not altered after OMTS was applied. These findings are supported by previous work proposing that the pre-TM1 region of the ␤ 2 subunit contributes to a pentobarbital-mediated activation pathway (Mercado and Czajkowski, 2008).…”
Section: Discussionsupporting
confidence: 81%
“…GABA A R Activation by PB Has Different Structural Requirements than GABA-Previous studies have shown that the structural elements underlying GABA A R activation by GABA and PB, which bind at different sites (25), are different (36,42,43). The differential effects of the glycine insertions on GABA and PB activation provide additional support for this idea.…”
Section: Discussionmentioning
confidence: 99%
“…First introduced into protein engineering in 1984 (32), double mutant cycle analysis was used to examine intramolecular and intermolecular interactions between proteins or a protein and its ligands (27,33,34). A double-mutant cycle involves a WT protein, two single mutants, and the corresponding double mutant protein.…”
Section: Double Mutant Cycle Analysis Indicates a Cooperative Mechanimentioning
confidence: 99%